Cover Image, Volume 94, Number 8, August 2022. Issue 8 (14th June 2022) - Huo, Shuting; Hai, Yan; Guo, Yaxin; Nie, Li; Li, Hongmei; Qiao, Peiwen; Zong, Kexin; Li, Xin; Guo, Yuanyuan; Song, Jingdong; Zhao, Honglan; Lei, Wenwen; et al.
Abstract : Front Cover Caption : The cover image is based on the Research Article Intrahost variation and evolutionary dynamics of adenoviruses correlate to neutrophils in infected patients by Shuting Huo et al., https://doi.org/10.1002/jmv.27744 .